ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN AKUNTANSI KEUANGAN DAERAH PADA RUMAH SAKIT UMUM DAERAH (RSUD) ARIFIN AHMAD PEKANBARU - Azizah, Nur (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
The purpose of research is to compare the financial performance of general hospitals (Hospital)Arifin Achmad Pekanbaru both before and after referring to the financial accounting areacontained in the Ministerial Regulation No. 13 in the country in 2006. Data collection techniquesused were interviews and documentation techniques. Data were analyzed using four variables:the ratio of the area of financial independence, effectiveness and efficiency ratio of local revenues,the ratio of the activity, and growth ratios. The results of this study indicate that there aredifferences in financial performance before and after the application of financial accounting areain general hospitals (Hospital) Arifin Achmad Pekanbaru.. It is evident from the results of theanalysis, in which the ratio of the area of financial independence before the issuance of thefinancial accounting area which decreased after the implementation of accounting and financeareas which increased. PAD-effectiveness ratio was highest in the year 2007 in the amount of100.44% and the lowest occurred. PAD efficiency ratios ranged from 39.78% to 56.30%.Routine expenditure ratio in 2006 and 2009 ranged from 55.80% to 95.91%, and developmentspending in 2006 to 2009 ranged from 3.88% to 4.59%. This shows the ratio of budget growingRegional General Hospital Arifin Achmad Pekanbaru in fiscal year 2006 to 2009 showed positivegrowth despite reduced growth trend.Keywords : financial accounting regional and financial performance